Preparation method of alumina-based thermal insulation material with controllable pore structure

By using the combination of waste alumina and different standards of magnesium oxide, the use of particles accumulation and volume expansion effects is used to prepare aluminum oxide insulation materials to solve the problem of high cost, complex technology and pollution in existing technology, and achieve low cost, low cost, and achieve low cost, and achieve low cost, and achieve low cost, and achieve low cost, and achieve low cost, and achieve low cost, and achieve low cost. Simple and environmentally friendly insulation materials are prepared and improved product performance.

CN119371185APending Publication Date: 2025-01-28THE 52ND RES INST OF CHINA ORDNANCE IND GRP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411268004.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The existing alumina-based thermal insulation materials preparation methods have high cost, complex processes and pollution problems, and consume a lot of ore resources.

Method used

The main raw materials are used by waste oxide, combined with different standards of magnesium oxide as additives, and the coordinated effects of the pile stacking effect and the original volume expansion effect of the original position are prepared to prepare the controllable aluminum aluminum aluminum insulation and refractory ceramics.

Benefits of technology

Realize the preparation of low -cost, simple process, and pollution -free aluminum oxide base insulation materials, reduce the consumption of ore resources, and the product performance is controllable, and the thermal conductivity and mechanical properties are improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method of an alumina-based thermal insulation material with a controllable pore structure, and the specific technical scheme is as follows: firstly uniformly mixing 85-95% by mass of waste alumina powder and 5-15% by mass of a magnesium oxide additive, then pressing into a green body by a cold isostatic press under 10-30MPa, and finally calcining the green body at 1100-1200 DEG C for 2-4 hours to obtain the alumina-based thermal insulation material with the controllable pore structure. And cooling along with the furnace to obtain the alumina-based thermal insulation material. The raw materials used in the invention are industrial wastes, and non-renewable ore resources are replaced, so that the resource recycling efficiency is improved while a large amount of cost is saved. The pore structure of the prepared thermal insulation material can be regulated and controlled by adjusting the granularity and proportion of the magnesium oxide additive, the porosity is further increased, the heat conductivity coefficient is reduced, the comprehensive performance is greatly improved, and the thermal insulation material is suitable for large-scale industrial popularization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heat-insulating material preparation, and in particular relates to an alumina-based heat-insulating refractory ceramic with controllable pore structure and a preparation method thereof. Background Art

[0002] Porous refractory materials, also known as lightweight refractory materials, are the most important type of thermal insulation refractory materials. They are usually defined as refractory materials with a true porosity of ≥45%. The main difference between porous refractory materials and dense refractory materials is the pore structure, and these variable pore structures inside porous refractory materials are also the key to their thermal insulation performance. Typical preparation methods for porous refractory materials include foaming method, pore-forming agent method, starch consolidation method, gel-sol method, particle accumulation method and in-situ decomposition pore method. However, the existing preparation methods all have some shortcomings. For example, the foaming method requires the use of chemical reagents such as foaming agents that have potential risks to the environment, the starch consolidation method and the gel-sol method have complex process flows, and the pore size of the pore-forming agent method is difficult to control. Therefore, in order to promote the development and application of thermal insulation materials, it is urgent to develop a preparation method with low cost, simple process and pollution-free characteristics.

[0003] Alumina-based thermal insulation materials are a relatively important type of thermal insulation materials. They belong to the category of high-temperature thermal insulation materials (the operating temperature can reach above 1200°C) and are usually prepared from high-alumina bauxite ore raw materials. However, in recent years, the price of raw ore has been rising steadily, and the need for environmental protection has led to a corresponding increase in its preparation cost. Therefore, the development of low-cost raw materials that can be used to prepare alumina-based thermal insulation materials can not only help alleviate the environmental problems caused by excessive mine development, but also benefit the sustainable development of alumina-based thermal insulation materials and thermal insulation materials. Summary of the invention

[0004] The present invention aims to overcome the defects of the prior art, with the purpose of saving non-renewable precious ore resources and reducing the preparation cost of alumina-based thermal insulation materials, and at the same time develops a kind of alumina-based thermal insulation refractory ceramic with controllable pore structure and the preparation method thereof with the characteristics of low cost, simple process and no pollution. Specifically, the present invention uses waste alumina as the main raw material and magnesium oxide of different scales (submillimeter, micrometer and nanometer) as an additive, and produces a low-cost, high-performance alumina-based thermal insulation material through the synergistic effect of particle accumulation effect and in-situ volume expansion effect.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] The first step is to crush the waste alumina to less than 75μm (passing a 200 mesh sieve);

[0007] The second step is to mix the waste alumina powder and the magnesium oxide additive evenly according to the mass fraction of 85% to 95% and 5% to 15%;

[0008] The third step is to press the mixed powder into a green body at 10-30 MPa;

[0009] The fourth step is to calcine the green body at 1100-1200° C. for 2-4 hours and obtain the alumina-based thermal insulation material by cooling the furnace.

[0010] Furthermore, the waste aluminum oxide in the first step is one or more of waste abrasives, waste furnace tubes, waste crucibles, waste thermocouple protection tubes, and waste electrical insulating substrates whose main component is aluminum oxide phase;

[0011] Furthermore, the magnesium oxide additive in the second step is one or more of submicron magnesium oxide (≤75 μm), micron magnesium oxide (≤5 μm) and nano magnesium oxide (≤50 nm);

[0012] In the green body forming stage, pores are mainly formed by the particle stacking effect, so large-sized additives are required (to form uniformly distributed large pores in the green body to ensure sufficient porosity). However, if the size of the additive is too large, the green body strength will be too low, and the uneven shrinkage in the later heat treatment stage will easily form sintering crack defects. In the heat treatment stage, pores are mainly formed by the in-situ volume expansion effect (the volume expansion of about 8% will occur during the formation of magnesium-aluminum spinel by aluminum oxide and magnesium oxide. The present invention is the first to propose pore formation by the volume expansion effect of magnesium-aluminum spinelization, and no other patents with similar concepts have been retrieved), so small-sized additives are required (to form small pores, regulate the pore structure to further reduce the thermal conductivity and improve the interface strength). However, if all nano-magnesium oxide is used, the raw material cost pressure will be too high. Therefore, considering the preparation cost and product performance, the preferred magnesium oxide additives of the present invention are submicron magnesium oxide (≤75μm), micron magnesium oxide (≤5μm) and nano magnesium oxide (≤50nm).

[0013] Furthermore, the green compact is pressed by cold isostatic pressing in the third step;

[0014] The traditional pressing method is mostly uniaxial pressing. The disadvantage of this method is that the specimen is subjected to uneven force, which will cause uneven distribution of pores inside the green body, affecting product quality (especially the stability of performance). Therefore, the present invention is preferably a cold isostatic pressing method, which makes the pores inside the green body evenly distributed, making it easy to control the pore structure and other corresponding properties of the product through subsequent heat treatment.

[0015] The present invention discloses the following technical effects:

[0016] First, it has environmental advantages. The main raw material of the present invention is industrial solid waste, which has a large output and a wide range of sources. Recycling it into thermal insulation materials not only solves the problem of difficult treatment of solid waste accumulation, but also saves mineral resources. Although additives will increase some costs, their dosage is small (no more than 15%), and the unit price is low, so the cost is still much lower than the traditional method of using bauxite or chemical raw materials. Therefore, it can provide an effective reference for the material utilization of industrial solid waste and the preparation of low-cost thermal insulation materials.

[0017] Second, it has process advantages. The preparation process of the present invention has the characteristics of simple process, easy operation, and no pollution. Compared with the traditional gel-sol method, starch consolidation method and foaming method, in addition to simpler process steps, it also saves chemical raw materials such as cross-linking agents and foaming agents, and will not cause environmental problems.

[0018] Third, it has performance advantages. The product performance of the present invention is controllable, especially the thermal conductivity. Compared with the traditional pore-forming agent method and the particle accumulation method, since the pore structure can be regulated by adjusting the type and content of the magnesium oxide additive, a multi-scale (submillimeter / micrometer / submicrometer / micrometer) and multi-type (open pore / closed pore) pore structure can be prepared, so as to further change certain properties of the product in a directional manner (such as increasing the addition amount of submillimeter magnesium oxide to increase the product porosity and open porosity ratio to reduce thermal conductivity, or increasing the addition amount of nano magnesium oxide to increase the closed porosity ratio and the degree of interface bonding to improve mechanical properties). In addition, the theoretical thermal conductivity of the second phase of magnesium-aluminum spinel formed by the reaction of magnesium oxide additives is lower than that of aluminum oxide, so its formation is not only adjustable pores, but also beneficial to increase the interface bonding strength and the thermal conductivity of the solid phase.

[0019] The key performance indicators of the alumina-based thermal insulation material prepared by the present invention are as follows: the apparent porosity is 55.3% to 61.8%, the volume density is 1.35 to 1.49 g / cm 3 The room temperature compressive strength is 5.1~18.8MPa, and the maximum value of thermal conductivity at 25~1200℃ is 0.39~0.65W / (m·K). DETAILED DESCRIPTION

[0020] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0021] Example 1

[0022] The first step is to crush the waste alumina (waste alumina abrasive) to less than 75 μm (passing a 200 mesh sieve);

[0023] The second step is to mix the waste alumina powder and the magnesium oxide additive (submicron magnesium oxide) evenly according to the mass fractions of 95% and 5%;

[0024] The third step is to press the mixed powder into a green body by a cold isostatic press at 10 MPa;

[0025] The fourth step is to calcine the green body at 1100° C. for 2 hours and obtain an alumina-based thermal insulation material while cooling the furnace.

[0026] After testing, the performance indicators of the alumina thermal insulation material prepared in this embodiment are as follows: the apparent porosity is 61.8%, the pore size is a single peak distribution with an average size of 0.64 μm, and the volume density is 1.35 g / cm 3 The room temperature compressive strength is 5.1MPa, and the maximum thermal conductivity at 25-1200℃ is 0.39W / (m·K).

[0027] Example 2

[0028] The first step is to crush the waste alumina (waste electrical insulation substrate) to less than 75 μm (passing a 200 mesh sieve);

[0029] The second step is to mix the waste alumina powder and the magnesium oxide additive (80% of submicron magnesium oxide + 20% of nano magnesium oxide) evenly according to the mass fraction of 90% and 10%;

[0030] The third step is to press the mixed powder into a green body by a cold isostatic press at 30 MPa;

[0031] The fourth step is to calcine the green body at 1150° C. for 3 hours and cool it in the furnace to obtain an alumina-based thermal insulation material.

[0032] After testing, the performance indicators of the alumina thermal insulation material prepared in this embodiment are as follows: the apparent porosity is 61.3%, the pore size is bimodal distribution with an average size of 0.56 μm, and the volume density is 1.35 g / cm 3 The room temperature compressive strength is 6.9MPa, and the maximum thermal conductivity at 25-1200℃ is 0.43W / (m·K).

[0033] Compared with Example 1, the additive in this example is a mixture of submicron magnesium oxide and nano-magnesium oxide, so the pores of the prepared thermal insulation material show a bimodal distribution, and the average pore size is slightly reduced. When the material is damaged, the small-sized pores can delay stress damage through the crack deflection enhancement effect, and ultimately show better strength performance.

[0034] Example 3

[0035] The first step is to crush the waste alumina (waste thermocouple protection tube) to less than 75μm (passing through a 200-mesh sieve);

[0036] The second step is to mix the waste alumina powder and the magnesium oxide additive (70% of micron-grade magnesium oxide + 30% of nano-grade magnesium oxide) evenly according to the mass fractions of 90% and 10% respectively;

[0037] The third step is to press the mixed powder into a green body by a cold isostatic press at 30 MPa;

[0038] The fourth step is to calcine the green body at 1150° C. for 3 hours and cool it in the furnace to obtain an alumina-based thermal insulation material.

[0039] After testing, the performance indicators of the alumina thermal insulation material prepared in this embodiment are as follows: the apparent porosity is 59.8%, the pore size is bimodal distribution with an average size of 2.83 μm, and the volume density is 1.38 g / cm 3 The room temperature compressive strength is 10.6MPa, and the maximum thermal conductivity at 25-1200℃ is 0.46W / (m·K).

[0040] Example 4

[0041] The first step is to crush the waste alumina (waste abrasive and waste furnace tube) to less than 75μm (passing through a 200 mesh sieve);

[0042] The second step is to mix the waste alumina powder and the magnesium oxide additive (60% of micron-grade magnesium oxide + 20% of submicron-grade magnesium oxide + 20% of nano-grade magnesium oxide) in a mass fraction of 85% and 15% respectively;

[0043] The third step is to press the mixed powder into a green body by a cold isostatic press at 20 MPa;

[0044] The fourth step is to calcine the green body at 1200° C. for 2 hours and obtain an alumina-based thermal insulation material while cooling the furnace.

[0045] After testing, the performance indicators of the alumina thermal insulation material prepared in this embodiment are as follows: the apparent porosity is 61.3%, the pore size is trimodal distribution with an average size of 2.17 μm, and the volume density is 1.36 g / cm 3 The room temperature compressive strength is 9.7MPa, and the maximum thermal conductivity at 25-1200℃ is 0.51W / (m·K).

[0046] Compared with Example 3, the additives in this example are also mixed in multiple sizes, so the pores of the prepared thermal insulation material are multi-modal distributed. At the same time, due to the introduction of the submicron level, the average pore size of the prepared material is slightly reduced and the apparent porosity is increased.

[0047] Example 5

[0048] The first step is to crush the waste alumina (waste crucible) to less than 75 μm (passing through a 200 mesh sieve);

[0049] The second step is to mix the waste alumina powder and the magnesium oxide additive (micron-grade magnesium oxide) evenly according to the mass fractions of 85% and 15%;

[0050] The third step is to press the mixed powder into a green body by a cold isostatic press at 20 MPa;

[0051] The fourth step is to calcine the green body at 1200° C. for 3 hours and obtain the alumina-based thermal insulation material while cooling the furnace.

[0052] After testing, the performance indicators of the alumina thermal insulation material prepared in this embodiment are as follows: the apparent porosity is 59.4%, the pore size is a single peak distribution with an average size of 3.44 μm, and the volume density is 1.39 g / cm 3 The room temperature compressive strength is 12.8MPa, and the maximum thermal conductivity at 25-1200℃ is 0.49W / (m·K).

[0053] Example 6

[0054] The first step is to crush the waste alumina (waste thermocouple protection tube) to less than 75μm (passing through a 200-mesh sieve);

[0055] The second step is to mix the waste alumina powder and the magnesium oxide additive (50% of submillimeter magnesium oxide + 50% of nano-magnesium oxide) evenly according to the mass fraction of 85% and 15%;

[0056] The third step is to press the mixed powder into a green body by a cold isostatic press at 30 MPa;

[0057] The fourth step is to calcine the green body at 1200° C. for 3 hours and obtain the alumina-based thermal insulation material while cooling the furnace.

[0058] After testing, the performance indicators of the alumina thermal insulation material prepared in this embodiment are as follows: the apparent porosity is 60.3%, the pore size is bimodal distribution with an average size of 17.92 μm, and the volume density is 1.38 g / cm 3 The room temperature compressive strength is 13.9MPa, and the maximum thermal conductivity at 25-1200℃ is 0.48W / (m·K).

[0059] Example 7

[0060] The first step is to crush the waste alumina (waste electrical insulation substrate) to less than 75 μm (passing a 200 mesh sieve);

[0061] The second step is to mix the waste alumina powder and the magnesium oxide additive (nano-grade magnesium oxide) evenly according to the mass fractions of 95% and 5%;

[0062] The third step is to press the mixed powder into a green body by a cold isostatic press at 30 MPa;

[0063] The fourth step is to calcine the green body at 1200° C. for 4 hours and obtain the alumina-based thermal insulation material while cooling the furnace.

[0064] After testing, the performance indicators of the alumina thermal insulation material prepared in this embodiment are as follows: the apparent porosity is 55.3%, the pore size is a single peak distribution with an average size of 0.16 μm, and the volume density is 1.49 g / cm 3 The room temperature compressive strength is 18.8MPa, and the maximum thermal conductivity at 25-1200℃ is 0.65W / (m·K).

Claims

1. A method for preparing an alumina-based thermal insulation material with controllable pore structure, characterized in that: The following steps are involved: (1) Crushing the waste alumina to less than 75 μm; (2) mixing the waste alumina powder and the additive magnesium oxide in a mass percentage of 85% to 95% and 5% to 15%; (3) pressing the mixed powder into a green compact at 10-30 MPa; (4) calcining the green body at 1100-1200° C. for 2-4 hours and cooling the furnace to obtain an alumina-based thermal insulation material.

2. The preparation method according to claim 1, characterized in that: The waste alumina in step (1) is one or more of waste abrasives whose main component is alumina phase, waste furnace tubes, waste crucibles, waste thermocouple protection tubes, and waste electrical insulating substrates.

3. The preparation method according to claim 1, characterized in that: The magnesium oxide additive in step (2) is one or more of submicron magnesium oxide with a particle size of ≤75 μm, micron magnesium oxide with a particle size of ≤5 μm, and nanometer magnesium oxide with a particle size of ≤50 nm.

4. The preparation method according to claim 1, characterized in that: The pressing method for forming the green body in step (3) is cold isostatic pressing.

Citation Information

Patent Citations

  • Lightweight micro closed cell magnesium-containing corundum refractory aggregate and preparation method thereof

    CN104446543A

  • Gradiently composed microporous corundum-spinel material and preparation method thereof

    CN108409308A

  • Aluminum oxide light thermal insulation material and preparation method thereof

    CN110937882A

  • Lightweight periclase-magnesium aluminate spinel refractory material and preparation method thereof

    CN118125843A

  • AU2020102254A4